Принципи математичного моделювання когенераційних систем на базі газотурбінних установок - Дмитроченкова, Елла (Видавництво Національного університету «Львівська політехніка», 2009)
Necessity of mathematical modeling and optimization of working processes for a choice of the circuit and parameters such as heat power installation is considered. The description of mathematical models of the basic groups of elements cogeneration installations is resulted and four primary goals solved at calculation of their characteristics are formulated. The mathematical model of effective efficiency of a cycle of gas turbine installations is received.
Keywords: mathematical modeling; optimization of working processes; cogeneration installations; gas turbine installation